RYR2 mutation in non‐small cell lung cancer prolongs survival via down‐regulation of DKK1 and up‐regulation of GS1‐115G20.1: A weighted gene Co‐expression network analysis and risk prognostic models. Issue 2 (7th December 2021) - Ren, Wenjun; Li, Yongwu; Chen, Xi; Hu, Sheng; Cheng, Wanli; Cao, Yu; Gao, Jingcheng; Chen, Xia; Xiong, Da; Li, Hongrong; Wang, Ping
Abstract: RYR2 mutation is clinically frequent in non‐small cell lung cancer (NSCLC) with its function being elusive. We downloaded lung squamous cell carcinoma and lung adenocarcinoma samples from the TCGA database, split the samples into RYR2 mutant group ( n = 337) and RYR2 wild group ( n = 634), and established Kaplan‐Meier curves. The results showed that RYR2 mutant group lived longer than the wild group ( p = 0.027). Weighted gene co‐expression network analysis (WGCNA) of differentially expressed genes (DEGs) yielded prognosis‐related genes. Five mRNAs and 10 lncRNAs were selected to build survival prognostic models with other clinical features. The AUCs of 2 models are 0.622 and 0.565 for predicting survival at 3 years. Among these genes, the AUCs of DKK1 and GS1‐115G20.1 expression levels were 0.607 and 0.560, respectively, which predicted the 3‐year survival rate of NSCLC sufferers. GSEA identified an association of high DKK1 expression with TP53, MTOR, and VEGF expression. Several target miRNAs interacting with GS1‐115G20.1 were observed to show the relationship with the phenotype, treatment, and survival of NSCLC. NSCLC patients with RYR2 mutation may obtain better prognosis by down‐regulating DKK1 and up‐regulating GS1‐115G20.1 .